Two mutations in troponin I that cause hypertrophic cardiomyopathy have contrasting effects on cardiac muscle contractility. - Burton, D; Abdulrazzak, H; Knott, A; Elliott, K; Redwood, C; Watkins, H; Marston, S; Ashley, C (2002)
We investigated the effects of two mutations in human cardiac troponin I, Arg(145)-->Gly and Gly(203)-->Ser, that are reported to cause familial hypertrophic cardiomyopathy. Mutant and wild-type troponin I, overexpressed in Escherichia coli, were used to reconstitute troponin complexes in vanadate-treated guinea pig cardiac trabeculae skinned fibres, and thin filaments were reconstituted with human cardiac troponin and tropomyosin along with rabbit skeletal muscle actin for in vitro motility and actomyosin ATPase assays. Troponin containing the Arg(145)-->Gly mutation inhibited force in skinned trabeculae less than did the wild-type, and had almost no inhibitory function in the in vitro motility assay. There was an enhanced inhibitory function with mixtures of 10-30% [Gly(145)]troponin I with the wild-type protein. Skinned trabeculae reconstituted with troponin I containing the Gly(203)-->Ser mutation and troponin C produced less Ca(2+)-activated force (64+/-8% of wild-type) and demonstrated lower Ca(2+) sensitivity [Delta(p)Ca(50) (log of the Ca(2+) concentration that gave 50% of maximal activation) 0.25 unit (P<0.05)] compared with wild-type troponin I, but thin filaments containing [Ser(203)]-troponin I were indistinguishable from those containing the wild-type protein in in vitro motility and ATPase assays. Thus these two mutations each result in hypertrophic cardiomyopathy, but have opposite effects on the overall contractility of the muscle in the systems we investigated, indicating either that we have not yet identified the relevant alteration in contractility for the Gly(203)->Ser mutation, or that the disease does not result directly from any particular alteration in contractility.